Ulnar Nerve Decompression With Subcutaneous Transposition - Kevin Jurgensmeier MD; Abhinav Lamba BS; Jonathan D. Barlow MD; Joaquin Sanchez-Sotelo MD, PhD; Christopher L. Camp MD (SAGE Publishing, 2024)
Background: Medial-sided elbow injuries are becoming increasingly common among throwing athletes due to overuse and increased specialization at early ages. High valgus stress and repetitive elbow flexion/extension during throwing not only affects the ligaments and dynamic support of the elbow, but commonly affects the ulnar nerve. Indications: Management of cubital tunnel syndrome is initially rest, therapy, and functional training; however, if conservative measures do not appropriately address the ulnar neuropathy, surgical decompression with subcutaneous transposition is a reliable treatment option. Technique Description: An incision is created over the medial epicondyle. The medial antebrachial cutaneous nerve is identified and protected. The ulnar nerve is identified and tagged with a vessel loop to allow for appropriate handling of the nerve. Decompression of the ulnar nerve begins proximally by spreading the tissues superficial to the ulnar nerve and splitting the fascia overlying it. Then, dissection deep to the nerve is performed. A small strip of the medial intermuscular septum will be used as a sling to hold the nerve securely in the transposed position. This is released proximally and the distal attachment to the medial epicondyle is left in place. Decompression is then continued distally by releasing the superficial fascia over the flexor carpi ulnaris (FCU) and a portion of the deep FCU muscle belly and fascia. The nerve is decompressed circumferentially, while preserving penetrating branches to the FCU as able. Ultimately, the ulnar nerve is decompressed 10 cm proximal and 10 cm distal to the medial epicondyle. The intermuscular septum is then pulled over the nerve, checked for appropriate length, and sutured in place both posterior and anterior to the ulnar nerve. Results: Symptom improvement after decompression and transposition is high (>90%); however, performance outcomes in overhead and throwing athletes is variable, and return to previous or higher level of play ranges from 60% to 90%. Discussion/Conclusion: Ulnar nerve decompression and transposition can reliably address underlying symptoms, but results are mixed for return to sport outcomes in overhead and throwing athletes. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.